2020
DOI: 10.1101/2020.12.11.421784
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conformational Ensembles of Non-Coding Elements in the SARS-CoV-2 Genome from Molecular Dynamics Simulations

Abstract: The 5’ untranslated region (UTR) of the SARS-CoV-2 genome is a conserved, functional and structured genomic region consisting of several RNA stem-loop elements. While the secondary structure of such elements has been determined experimentally, their three-dimensional structure is not known yet. Here, we predict structure and dynamics of five RNA stem loops in the 5’-UTR of SARS-CoV-2 by extensive atomistic molecular dynamics simulations, more than 0.5ms of aggregate simulation time, in combination with enhance… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…However, in the secondary structure prediction using CentroidFold [ 61 ] and the reference sequence, these base pairs were predicted to exist in more than 92% of the ensemble. Furthermore, a recent study [ 59 ] showed that, even with a rigorous extended ensemble simulation, the hairpin structure remained intact. Given these results, the drawback of structural restraints to SL1 is expected to be minimal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the secondary structure prediction using CentroidFold [ 61 ] and the reference sequence, these base pairs were predicted to exist in more than 92% of the ensemble. Furthermore, a recent study [ 59 ] showed that, even with a rigorous extended ensemble simulation, the hairpin structure remained intact. Given these results, the drawback of structural restraints to SL1 is expected to be minimal.…”
Section: Resultsmentioning
confidence: 99%
“…First, as we explained in "Convergence of the extended ensemble simulation", even though the current simulation uses the extended ensemble method, it is difficult to achieve full convergence. Sampling RNA structures are generally considered difficult even with the small system size, [55][56][57][58][59] and so does sampling the protein-RNA interaction. Given the length of IDR and the size of RNAs, the convergence of the simulation may be beyond the capability of the current computational resources.…”
Section: Limitations Of This Studymentioning
confidence: 99%